Productivity and profitability of drip fertigated wheat (Triticum aestivum) – mungbean (Vigna radiata) – maize (Zea mays) cropping system - DHAYAL, DIANA; LAL, KHAJANCHI; SINDHU, VINAY KUMAR; KHANNA, MANOJ; SUDHISHRI, SUSAMA; SINGH, MAN; BHATTACHARYYA, R; ROSIN, K G; CHAKRABORTY, D (The Indian Journal of Agricultural Sciences, 2023)
An experiment was conducted at the research farm of ICAR-Indian Agricultural Research Institute, New Delhi during 2019–20 and 2020–21 to study the productivity and economic viability of wheat (Triticum aestivum L.)– mungbean (Vigna radiata (L.) R. Wilczek)–maize (Zea mays L.) fertigated with 0, 60, 80, 100% recommended doses of NPK and irrigated at 0.6 and 0.8 crop evapotranspiration (ETc) through subsurface (SSDI) and surface drip irrigation (SDI). The results were compared with the conventional practice of surface irrigation and soil application of 100% recommended doses of NPK. Grain yields of wheat, mungbean, maize and system wheat equivalent yield (SWEY) improved by 22.9, 7.2, 21.9 and 19.4%, respectively with increase in NPK fertigation doses from 60 to 100% and by 15.6, 9.2, 4.9 and 9.7% with the increase in irrigation frequency from 0.6 to 0.8 ETc. However, SDI and SSDI had equal system productivity (12.48 and 12.85 Mg/ha). The SWEY at 0.8ETc fertigated either with NPK80 or NPK100 was statistically at par (14.2–15.9 Mg/ha) with the conventional practice (14.3–15.2 Mg/ha). The cash inflow, net income and benefit cost ratio (BCR) of the cropping system also increased successively with increase in fertigation doses and irrigation frequency. The net income and BCR followed the order maize>wheat>mungbean. The net income under SSDI at 0.8 ETc with NPK80 or NPK100 in wheat, mungbean, maize and system was 11–13, 88–105, 1-9 and 8–14% higher than the conventional practice. At 0.8 ETc and NPK100, BCR in SSDI (1.86) was higher than in SDI (1.71) and conventional system (1.67).